2022
DOI: 10.15625/2615-9023/16628
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of biosynthesizing folate, riboflavin and typical probiotic traits reveal the potential use of \(\textit{Lactobacillus plantarum}\) LCN13 as a feed additive for swine farming

Abstract: Lactic acid bacteria have been advocated as probiotics to replace antibiotic growth promoters, improve growth performance, and reduce cost production in swine farming. The aim of this study is to identify and evaluate the probiotic traits of strain LCN13 isolated from traditionally fermented feed for swine. Thirty-five bacterial isolates with different morphological characteristics were isolated, among which 9 isolates showed the ability to produce lactic acid and antibacterial activity against pathogenic bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Notably, the NDF value (27.9 2± 1.13 % DM) after 120 h of ensilage was reduced to approximately that of basal diet (24.02 ± 1.44 % DM). This might have occurred because the strain L. plantarum LCN13 and/or both B. velezensis VTX9 and S. cerevisiae MCN9 produced extracellular enzymes such as cellulase that decomposes cellulose and other biopolymer contents including hemicellulose, lignin, and pectin present in plants (Nguyen et al 2022). The obtained results were also consistent with previous studies indicating the advantages of microbial inoculants over a single strain (Turyk et al, 2014;Luo et al, 2021).…”
Section: Effect Of Microbial Inoculants On Fermentation Characteristicssupporting
confidence: 90%
See 4 more Smart Citations
“…Notably, the NDF value (27.9 2± 1.13 % DM) after 120 h of ensilage was reduced to approximately that of basal diet (24.02 ± 1.44 % DM). This might have occurred because the strain L. plantarum LCN13 and/or both B. velezensis VTX9 and S. cerevisiae MCN9 produced extracellular enzymes such as cellulase that decomposes cellulose and other biopolymer contents including hemicellulose, lignin, and pectin present in plants (Nguyen et al 2022). The obtained results were also consistent with previous studies indicating the advantages of microbial inoculants over a single strain (Turyk et al, 2014;Luo et al, 2021).…”
Section: Effect Of Microbial Inoculants On Fermentation Characteristicssupporting
confidence: 90%
“…Moreover, as expected, the addition of microbial mixtures accelerated production of organic acids such as lactic acid, while lowering silage pH. Nguyen's study (2022) determined that L. plantarum LCN13 strain had a strong capability to produce lactic acid up to 18.5 ± 0.31 g/L and resist silage pH 2 (Nguyen et al, 2022). In this study, a significant reduction of pH value was only observed in 1% and 1.5% microbial mixtures, at pH 4.45 and pH 4.18, respectively, comparable to that of control at pH 6.5.…”
Section: Effect Of Microbial Inoculants On Fermentation Characteristicsmentioning
confidence: 68%
See 3 more Smart Citations